Contemporary Topics in Graduate Medical Education Volume 2 - Stawicki, Stanislaw P.; Firstenberg, Michael S.; Orlando, James P.; Papadimos, Thomas J. (IntechOpen, 2022)
Graduate medical education (GME) continues its decades-long evolution. Evidence-based approaches are increasingly transforming the way we educate, evaluate, and promote GME trainees. Key to this transformation is our ability to recognize that "medical education" constitutes a true lifelong continuum, beginning with pre-medical education, then proceeding to medical school, residency (and potentially subsequent fellowship) training, and then finally the so-called maintenance of certification that continues throughout one's entire professional career. This book explores a broad range of important topics, including the novel concept of "coping intelligence," the important role of "work-life integration," professional coaching and mentorship, professional development and career-long learning, patient-provider relationship, the impact of the COVID-19 pandemic on medical education, as well as the introduction of modern technologies to ameliorate the effects of social distancing. The book further discusses two important aspects of GME program management: the process of establishing new GME programs as well as the highly intricate process of merging residency programs. Different aspects and perspectives are incorporated, including those of residents, faculty, and program leadership. The book ends with chapters on diversity, equity and inclusion, and the importance of community-based medical education.